2006
DOI: 10.1142/9781860949104
|View full text |Cite
|
Sign up to set email alerts
|

Handbook of Pi and Pid Controller Tuning Rules

Abstract: This book, written by some of the main contributors to the subject, covers an important new perspective on PID control. The book is of interest to practicing engineers, graduate students, and researchers working in the systems and control area. The materials are understandable to average readers with a basic knowledge of systems and control. The book is very well written and can be used for self-study and as a reference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
144
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 393 publications
(147 citation statements)
references
References 10 publications
(1 reference statement)
0
144
0
3
Order By: Relevance
“…The PID•filter controller in Eq. (8) is an extension to the modified PID controller structure developed by Rivera et al [2], Horn et al [5], Lee et al [6] Shamsuzzoha and Lee [8][9][10] and Dwyer [11].…”
Section: Imc-pid Approach For Pid•filter Controller Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The PID•filter controller in Eq. (8) is an extension to the modified PID controller structure developed by Rivera et al [2], Horn et al [5], Lee et al [6] Shamsuzzoha and Lee [8][9][10] and Dwyer [11].…”
Section: Imc-pid Approach For Pid•filter Controller Designmentioning
confidence: 99%
“…Consider a general second-order plus dead time (SOPDT) process system, (11) where ζ is the damping factor. The process model is decomposed into P M =K/(τ 2 s 2 +2τζs+1) and P A =e −θs .…”
Section: Second-order Plus Dead Time Processmentioning
confidence: 99%
“…Assume that the real parameter a can be chosen arbitrarily, provided that the constraint a > 1 holds. Moreover, let u max be the value satisfying (14). If we define Q = u/a 2 , we can choose a so that: 1 + Q 2 m = β Q m , where Q m corresponds to u max and β > 0 is a new parameter depending on Q m and hence on a only.…”
Section: The Proposed Tuning Methodsmentioning
confidence: 99%
“…However, in spite of their central role in control engineering, PID have attracted relatively little attention of research community (see [1]). Only recently, indeed, many authors have observed that the practice of PID can take considerable benefits from specific research in this field (see [1,14]). Certainly, a better understanding of these control devices is highly desirable because it can contribute to enhance the quality of products and the efficiency of manufacturing.…”
mentioning
confidence: 99%
“…Each node i determines, based on the event intensity sensed by itself and by neighboring nodes, the normalized vectorx ie (t) directed toward the event, and modulates the intensity of the exchange forces by dynamically adapting G ik (t) so as to reach, at the equilibrium, the target inter-nodal distance. More specifically, G ik (t) is computed exploiting a first order Proportional Integrative (PI) controller driven by the error between the current distance d ik (t) and the target value d T ik (t) [19] . Notice that our solution does not require global knowledge of the absolute position of the event.…”
Section: Algorithmmentioning
confidence: 99%